Spatial Orientation: An Empirical Study on the Relevance of the Competency Area Spatial Orientation in the View of Society and Experts - Hemmer, Ingrid; Hemmer, Michael; Obermaier, Gabi; Uphues, Rainer (Journal of Geography Education, 2008)
The national standards for education in geography include six areas of competence. One of these areas is spatial orientation. This particular field includes topographical knowledge, categories of spatial imagination, the ability to orient one’s self in real space, and the use of maps and patterns of spatial perception. There is no discussion on the meaning of spatial orientation in general, but it is still not determined which elements within the whole of geographical knowledge and abilities must be mastered by German students. This survey aims to feed this discussion. 172 prominent members of society and 110 experts on geography have been asked how they ranked certain topographical knowledges and abilities.